Web Application and Emulation for Traffic Monitoring Using Simulation Tool (The International Journal of Engineering & Information Technology (IJEIT), 2024)
In modern times, significance of mobile service sector progressed so fast in the world and it is major phenomenon in the development of telecommunications field. Wireless technology has got the ability to develop new communications systems, multimedia services and others. Related to the continued growth of the vehicular industry and the increasing needed of road safety a new concept in the communications field was born: vehicular ad hoc networks (VANET). Vehicular sensor network (VSNET) is a promising technology, which combines wireless communication offered by vehicular ad hoc networks (VANET) with sensing devices installed in vehicles. VSNET generates opportunity to develop the road-side sensor infrastructure of current Traffic Monitoring Systems (TMS). VANETs are getting more and more attention from car manufacturers and governments both because of the wide-range of applications and services they can provide, such as car assistance, road safety systems, crash avoidance, Internet access, etc. This paper provides a simulation and emulation study of the proposed platform design which focuses on the possibility of the use of simulation tools to help build and develop an effective traffic monitoring system, so this system provides useful information for both: the vehicle driver and the authorized person at the traffic control center in order to contribute reduce the negative effects of traffic congestion. A web application design and the simulation and emulation process is presented and open source simulator tool is used for this study namely-NCTUns-6.0 (National Chiao Tung University Network Simulator).